2005
DOI: 10.1107/s0907444905019451
|View full text |Cite
|
Sign up to set email alerts
|

Post-crystallization treatments for improving diffraction quality of protein crystals

Abstract: X-ray crystallography is the most powerful method for determining the three-dimensional structure of biological macromolecules. One of the major obstacles in the process is the production of high-quality crystals for structure determination. All too often, crystals are produced that are of poor quality and are unsuitable for diffraction studies. This review provides a compilation of post-crystallization methods that can convert poorly diffracting crystals into data-quality crystals. Protocols for annealing, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
184
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(192 citation statements)
references
References 45 publications
3
184
0
5
Order By: Relevance
“…The crystals were cryoprotected by slow transfer to artificial mother liquor supplemented with 30% PEG 400. The diffraction qualities of the crystals were improved significantly by extensive trials of dehydration (32). The crystals were dehydrated by stepwise transfer to a mother liquor containing 25% PEG 3350, 0.2 M di-ammonium citrate hexahydrate, and 0.2 M sodium thiocyanate and were equilibrated over the same mother liquor for 5 d before cryoprotection.…”
Section: Methodsmentioning
confidence: 99%
“…The crystals were cryoprotected by slow transfer to artificial mother liquor supplemented with 30% PEG 400. The diffraction qualities of the crystals were improved significantly by extensive trials of dehydration (32). The crystals were dehydrated by stepwise transfer to a mother liquor containing 25% PEG 3350, 0.2 M di-ammonium citrate hexahydrate, and 0.2 M sodium thiocyanate and were equilibrated over the same mother liquor for 5 d before cryoprotection.…”
Section: Methodsmentioning
confidence: 99%
“…GraFix is thus unlikely to cause artifacts that can be attributed to chemical fixation at intermediate resolution. We expect that glutaraldehyde or formaldehyde treatment might allow higher-resolution structure determination as it has been shown that high-resolution X-ray structures can be obtained in the presence of chemical fixation reagents 12,13 . We tested GraFix on various fragile complexes with low cellular copy number such as spliceosomes (Fig.…”
mentioning
confidence: 99%
“…9). The effect of dehydration on WbdD (an improvement in diffraction resolution from 8 to 2.2 Å ) is very pronounced when compared with other examples (Heras & Martin, 2005). However, a facile and easily implementable protocol may extend the utility of dehydration.…”
Section: Effect Of Dehydration On the Structurementioning
confidence: 97%
“…However, a facile and easily implementable protocol may extend the utility of dehydration. The procedure described here combines several previously published ideas (Kiefersauer et al, 2000;Heras & Martin, 2005) into an easy-to-use, low-cost and convenient workflow. It is not anticipated that this will necessarily lead to more success than other approaches, but it is straightforward and amenable to high throughput.…”
Section: Effect Of Dehydration On the Structurementioning
confidence: 99%